The potential of augmented reality and gamification in higher education. A case study on usability - Mejía Gracia, César Augusto; Hernández García, Rodrigo Aryan; Ladrón de Guevara Smith, Maridalia (Praxis, 2025)
Education is constantly evolving, and the use of information technologies offers opportunities to implement new methodologies and tools that improve the effectiveness of the educational process. This study evaluates the usability of an educational application that uniquely combines augmented reality (AR) and gamification in the context of university education, specifically within the Digital Marketing field. The research approach was descriptive and mixed, using the System Usability Scale (SUS) to measure the application’s usability. Surveys and statistical analyses were conducted to collect and interpret data on user perceptions of the tool’s effectiveness and ease of use. Key findings reveal that the combination of AR and gamification significantly enhances the educational experience for university students. The application received high scores for usability on the SUS scale, indicating that students found the tool intuitive and effective for reinforcing their knowledge. Notably, strong correlations were observed between ease of use, speed of learning, and knowledge reinforcement. Despite the positive reception, users pointed out areas where the application could be simplified to improve the overall user experience. The study underscores the importance of usability and user satisfaction in adopting AR in educational settings.